2023
DOI: 10.3389/fonc.2023.1142907
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 4 exerts an atypical role in breast cancer progression that is dependent on the enzymatic activity that targets the cell-surface annexin A2

Abstract: BackgroundLOX family members are reported to play pivotal roles in cancer. Unlike their enzymatic activities in collagen cross-linking, their precise cancer functions are unclear. We revealed that LOXL4 is highly upregulated in breast cancer cells, and we thus sought to define an unidentified role of LOXL4 in breast cancer.MethodsWe established the MDA-MB-231 sublines MDA-MB-231-LOXL4 mutCA and -LOXL4 KO, which stably overexpress mutant LOXL4 that loses its catalytic activity and genetically ablates the intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Bio-PLG added to the MDA-MB-231 cell culture was co-localized with S100A11 in most parts of the cell membrane before fixation treatment of the cells, which was also confirmed ( Figure 2B ). It was confirmed that the PLG attached to the plasma membrane surface leads to plasmin activity, which is much higher in parental cells than in the LOXL4 KO cells ( Figure 2C ) ( 7 ). In addition, the manifestation of enzymatic active-form plasmin from the PLG in the membrane fraction required S100A11 since siRNA-mediated lowered expression of S100A11 markedly obstructed the plasmin activity ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Bio-PLG added to the MDA-MB-231 cell culture was co-localized with S100A11 in most parts of the cell membrane before fixation treatment of the cells, which was also confirmed ( Figure 2B ). It was confirmed that the PLG attached to the plasma membrane surface leads to plasmin activity, which is much higher in parental cells than in the LOXL4 KO cells ( Figure 2C ) ( 7 ). In addition, the manifestation of enzymatic active-form plasmin from the PLG in the membrane fraction required S100A11 since siRNA-mediated lowered expression of S100A11 markedly obstructed the plasmin activity ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 79%
“…The multimerized annexin A2 also coordinates with abundant integrin-b1 on the cell surface, allowing the growth, migration, and invasion of TNBC cells. The newly identified machinery of plasmin activation works cooperatively with the integrin-b1-mediated pathway we formerly revealed (7), particularly for the invasion event.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations